Redesain Produk Headphone Berbahan Baku Kayu dengan House of Quality (HOQ) pada Perempuan Berhijab - Ayu Tiara Suci; Sugeng Waluyo; Yudi Syahrullah (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Many types of hearing devices are known, namely headsets, headphones, earphones, handsfree, etc. Headphones are simple hearing aid accessories used for listening and have the best sound quality because they are designed for audio-only. Headphone design is evolving, and one of them can be found in a unique wooden headphone design. Wood is an environmentally friendly material and has an interesting motif. Many headphone users are dominated by millennials, including women in Indonesia, who mostly use the hijab. However, there are not many headphone products designed specifically for women with hijab. This study aims to redesign wood-based headphones for hijab-wearing women based on customer requirements using HOQ. Headphone product design and development is carried out in a mixed product-driven and customer-driven manner. The type of research used is qualitative and quantitative research. Qualitative research through literature studies, preliminary studies, and interviews, while quantitative analysis is based on online questionnaires. In this study, the population was Muslim female students wearing the hijab at Jenderal Sudirman University. The sample used in this study was 150 respondents taken using purposive sampling, and the data collection method was using an online questionnaire. The data analysis used is validation and reliability tests on questionnaires, preparation of HOQ, and design drawings using SolidWorks. The results of this study indicate that product-driven is the addition of small speakers. At the same time, customer-driven (based on the order of technical response from most important) consists of the total cost of production, wood materials, headphones with on-ear type, wireless, and volume buttons.. Keywords: product design, HOQ, mixed product-driven and customer-driven